The role of the orthodontist in the early simulating plate rehabilitation of children with Down syndrome (Journal of Medical Science, 2014)
Introduction. Abnormalities in the oro-facial complex in children with Down syndrome can be corrected through oro-facial therapy which makes use of a palatal plate. Aim. The aim of this study was to present the therapeutic effects of orthodontic palatal plate therapy in children with Down syndrome. Material and methods. The study was conducted on 50 children with Down syndrome between the ages of 3 months and 2 years who were treated by means of stimulating plate therapy a period of two years. Results. The study found that in 50% children with Down syndrome who underwent palatal plate oro-facial rehabilitation there was a visual improvement of the mimetic muscles, tongue retraction as well as lip closure. Conclusions. The care by orthodontist and early palatal plate therapy ought to constitute an integral part of the comprehensive multidisciplinary rehabilitation of children with Down syndrome.